تحليل واقع بعض المؤشرات الدولية لمناخ الاستثمار في سورية - العلي, إبراهيم; الشيخ حسين, صطوف; ركاج, يحيى محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يُعد تواجد الجمهورية العربية السورية على قائمة المؤشرات الدولية بصورة عامة، وعلى قائمة المؤشرات الدولية للاستثمار بصورة خاصة، من أبرز الدلائل على الانفتاح الاقتصادي الموجه الذي تعيش مراحله سورية منذ بداية القرن الحالي. كما يُعدُّ الوقوف على عتبة هذه المؤشرات في غاية الأهمية لما تظهره من بعض نقاط القوة والضعف في اقتصاديات الدول التي تتعاطى معها، ولكونها محط أنظار قياصرة المال والاستثمار في العالم أجمع. إلا أن بوادر الأزمة المالية العالمية التي يشهدها العالم في هذه الأيام، وما يبديه بعضهم من نقد وتحفظ على طرق تعامل هذه المؤشرات مع البيانات الخاصة بسورية، يجعل من الوقوف على بعض هذه المؤشرات المؤثرة على الاستثمار في سورية أمراً ضرورياً. وقد توصلنا في نهاية هذا البحث إلى وجود تباين واضح في تأثير هذه المؤشرات على المناخ الاستثماري في سورية، ومن ثَمَّ جذب المزيد من الاستثمارات إليها . Generally, the Syrian Arab Republic’s existence on the list of the International Indicators, and especially on the investment's, is one of the clearest evidences of the directed economic openness that Syria has witnessed since the beginning of this Century. And the study of these indicators is considered too important as they show the good and bad of the countries' economies that dealing with them, and for they are the focus of the finance and investment tycoons in the whole world. But the eve of the global financial crisis taking place nowadays, and the reservation and criticism of the strategies with which those indicators make the focus on some of these indicators are necessary. We arrived, in conclusion, for obvious difference of the effect of the indicators on the Syrian investment climate, the attraction of more investment in Syria.